LITERASI ISLAM DALAM MANAJEMEN PEMBELAJARAN DI SEKOLAH DASAR: PENDEKATAN DAN IMPLEMENTASI - Muzammil Muzammil (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Literacy includes more than just the ability to read and write, but also the ability to think critically and analytically in understanding information. In Islamic education, literacy-based learning management is an important solution to improve the quality of learning. This approach integrates Islamic values with literacy skills, so that students not only understand religious knowledge but are also able to apply these values in everyday life. This study aims to analyze the strategy of literacy-based learning management in Islamic education at the Elementary School level, as well as to identify supporting and inhibiting factors. This study is expected to contribute to the development of a contextual and innovative Islamic education model. This study uses a literature study method to analyze the concept of literacy-based learning management in Islamic education in Elementary Schools. The results of the study indicate that literacy-based Islamic Education learning management plays a significant role in increasing students' interest in reading and writing. Islamic-based literacy not only hones reading and writing skills, but also helps students internalize the moral and spiritual values contained in Islamic texts. This increase in literacy skills strengthens students' abilities to analyze, organize ideas, and apply insights in everyday life. In addition, Islamic-based literacy contributes to the development of students' characters such as honesty, responsibility, and empathy. Teacher support in integrating literacy through relevant reading materials and active learning methods plays an important role in creating meaningful learning experiences. Therefore, Islamic education-based literacy strategies can be a solid foundation in forming a generation of intelligent Muslims with superior character.